2018
DOI: 10.1111/iwj.12929
|View full text |Cite
|
Sign up to set email alerts
|

Cellular interactions with bacterial cellulose: Polycaprolactone nanofibrous scaffolds produced by a portable electrohydrodynamic gun for point‐of‐need wound dressing

Abstract: Electrospun nanofibrous scaffolds are promising regenerative wound dressing options but have yet to be widely used in practice. The challenge is that nanofibre productions rely on bench-top apparatuses, and the delicate product integrity is hard to preserve before reaching the point of need. Timing is critically important to wound healing. The purpose of this investigation is to produce novel nanofibrous scaffolds using a portable, hand-held "gun", which enables production at the wound site in a time-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 30 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…Unaligned fibers with extremely low bead frequency were observed at the highest PCL ratio and by gradually decreasing the polymer ratio and increasing BC within the composite structures caused the bead density to increase. Previous studies have reported that increasing the BC concentration within the PCL-BC composites lead to an increase in bead occurrence [7]. Furthermore, incorporation of BC into other polymeric materials also resulted in similar outcomes [16,29].…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Unaligned fibers with extremely low bead frequency were observed at the highest PCL ratio and by gradually decreasing the polymer ratio and increasing BC within the composite structures caused the bead density to increase. Previous studies have reported that increasing the BC concentration within the PCL-BC composites lead to an increase in bead occurrence [7]. Furthermore, incorporation of BC into other polymeric materials also resulted in similar outcomes [16,29].…”
Section: Resultsmentioning
confidence: 80%
“…This is believed to be related to the aerodynamics in the spinning vessel (Figure 1), providing better evaporation and allowing the fiber jets to travel more and freely without being limited within closed chambers, eventually decreasing the fiber diameter and producing more promising fiber microstructures in the materials. Centrifugal spinning-based methods are devoid of an applied electric field and allow polymers without a charge to be spun with a large production rate [7,39].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Future work will employ portable medical devices to explore the potential to produce and deliver the functionalized fibers for point of care treatment. [ 59,60 ]…”
Section: Resultsmentioning
confidence: 99%
“…Polycaprolactone (PCL) was used as a carrier polymer along with 8 differing ratios of BC to generate BC-PCL composite nanofibres which could be exploited in use as emergency point-of-need wound care using a novel electrohydrodynamic gun (Aydogdu, M. O. et al, 2018). BC was processed into fibres after being suspended in dimethylformamide (DMF) and subjected to ultrasonication to form a gel-like solution that could be mixed with the PCL polymer solution.…”
Section: Electrospinningmentioning
confidence: 99%